Governing the reformed university - Ejersbo, Niels; Greve, Carsten; Pihl-Thingvad, Signe (Routledge, 2020)
Universities are important public institutions and are seen as key drivers for a country's economic and intellectual development. Their ability to deliver relevant research and education at the highest level have an impact on growth and progress in society, and governments attempt to control and govern the development of the universities. It is no longer left to the individual researcher or the institution to determine the role of the university.